Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.joep.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary job loss and changes in personality traits

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 42 publications
(58 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, Malmendier and Nagel (Malmendier and Nagel) document that individuals who experienced negative financial events such as the Great Depression exhibit a lower willingness to take financial risks. 91 Anger et al (2017) show that trauma can sometimes also result in positive changes in personality. Studying German data, they find 87 Elasticities of substitution are essentially the same at different stages of the life cycle.…”
Section: Evidence Frommentioning
confidence: 99%
“…Furthermore, Malmendier and Nagel (Malmendier and Nagel) document that individuals who experienced negative financial events such as the Great Depression exhibit a lower willingness to take financial risks. 91 Anger et al (2017) show that trauma can sometimes also result in positive changes in personality. Studying German data, they find 87 Elasticities of substitution are essentially the same at different stages of the life cycle.…”
Section: Evidence Frommentioning
confidence: 99%
“…In a meta-analysis conducted using longitudinal studies, Roberts et al (2006b) also showed statistically significant mean-level changes in Big Five personality traits in middle (40-60) and old (> 60) age. Personality changes can result from environmental changes in social roles or cultural milieu (Helson et al 2002a;Scollon and Diener 2006) or from life and work experiences (e.g., Roberts et al 2003;Roberts et al 2006a;Mroczek and Spiro 2003;Elkins et al 2017;Anger et al 2017;Golsteyn and Schildberg-Hörisch 2017).…”
Section: Description and Time Variability Of The Big Five Personalitymentioning
confidence: 99%
“…To tackle this problem, I follow Heineck and Anger (), Heineck (), and Nyhus and Pons () who regress the personality traits on age and age squared and use the residuals of these regressions for the analysis. Studies show (Anger et al ., ; Cobb‐Clark and Schurer, , ) that personality traits are mostly stable for at least 4 years and mostly stable around the age of 30 (Costa and McCrae, ). With a mean age of 40–42 years in all datasets, personality traits should mostly be stable.…”
Section: Datamentioning
confidence: 99%